2017
DOI: 10.3390/en10111696
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plant Growth Regulators on Cell Growth, Protein, Carotenoid, PUFAs and Lipid Production of Chlorella pyrenoidosa ZF Strain

Abstract: Abstract:In the present study, eight kinds plant growth regulators-salicylic acid (SA), 1-naphthaleneacetic acid (NAA), gibberellic acid (GA 3 ), 6-benzylaminopurine (6-BA), 2, 4-epi-brassinolide (EBR), abscisic acid (ABA), ethephon (ETH), and spermidine (SPD)-were used to investigate the impact on microalgal biomass, lipid, total soluble protein, carotenoids, and polyunsaturated fatty acids (PUFAS) production of Chlorella pyrenoidosa ZF strain. The results showed the quickest biomass enhancement was induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 70 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…Similar to salt stress, oxidative stress created by plant hormone in the present study also increased the carbon chain length and desaturation. The results in the present study were in agreement with those of Du et al [40] which showed that the plant hormone treatment and stress created by plant hormone especially IAA increased the carbon chain length and desaturation. Sivaramakrishnan and Incharoensakdi Biotechnol Biofuels (2020) 13:7 In case of gibberellic acid treatment which did not improve the omega-3 fatty acid content, it showed variations in the contents of linoleic and linolenic acid.…”
Section: Effect Of Different Plant Hormones On Fatty Acid Profilessupporting
confidence: 93%
See 4 more Smart Citations
“…Similar to salt stress, oxidative stress created by plant hormone in the present study also increased the carbon chain length and desaturation. The results in the present study were in agreement with those of Du et al [40] which showed that the plant hormone treatment and stress created by plant hormone especially IAA increased the carbon chain length and desaturation. Sivaramakrishnan and Incharoensakdi Biotechnol Biofuels (2020) 13:7 In case of gibberellic acid treatment which did not improve the omega-3 fatty acid content, it showed variations in the contents of linoleic and linolenic acid.…”
Section: Effect Of Different Plant Hormones On Fatty Acid Profilessupporting
confidence: 93%
“…(Table 2). Similarly, other plant hormones showed higher fatty acid desaturase expression than did the ABA treatment [40]. In addition, plant hormones could stimulate fatty acid elongation process.…”
Section: Effect Of Different Plant Hormones On Fatty Acid Profilesmentioning
confidence: 86%
See 3 more Smart Citations